POLITIK HUKUM TERHADAP PEREKONOMIAN DI INDONESIA - moh hudi (universitas islam darul ulum lamongan, 2018)
Politics is very important in determining economic policy in a country, especially a developing country like Indonesia. A political role is needed in determining progress policies. As a means of realizing the ideals that are in line with the opening of the fourth edition of the 1945 Constitution (UUD 1945). The economy can progress whether or not it is strongly influenced by politics. To determine so that politics can run well, the right law is needed to regulate politics especially in determining economic policy. The opposite is true if the law is not good, the politics are not good, then the economy cannot run well either. Thus harmony between the three is needed.